Non-Linearity In Monetary Models Of Exchange Rate In Five Asean Countries - Liew, Khim Sen (2008)

(untitled)
This study is a part of the research endeavor since 1970s in searching for a satisfactory exchange rate forecasting model. The main objective is to evaluate the forecast performance of the relevant monetary exchange rate models, which are determined by the linear and non-linear approaches. Particularly, the long-run cointegration relationship between yen-based currencies of five major South East Asian countries including Indonesia, Malaysia, Singapore, Thailand and the Philippines (collectively known as ASEAN-5) and their fundamentals are investigated using the carefully designed testing procedures that include integration order, cointegration and exogeneity tests. The set of potential exchange rate determinants including domestic and Japanese money supplies, aggregate output levels, aggregate price levels and interest rates are included in this study. In this respect, several versions of monetary exchange rate models are considered. The lately developed non-linear stationary and non-linear cointegration tests are also employed aiming to provide complementary if not improvement to the robustness of conventional tests. Towards the end of this study, the valid monetary exchange rate models are estimated for the ultimate purpose of forecast performance evaluation. The major finding of this study is that both the purchasing power parity model and the reduced form forward-looking monetary model can have excellence predictive power for the dynamic behaviour of yen-based ASEAN-5 nominal exchange rates, over forecast horizon of 24 months or less, based non-linear smooth transition regression (STR) modeling procedures. Hence, this study is able to provide evidence to contradict the assertion that empirical exchange rate models have weak predictive power at horizons less than two years (Lycons, 2002). Importantly, the empirical forecasting performance of non-linear STR modeling procedures is for the first time revealed in this study. Besides, this study identifies that, as far as ASEAN-5 is concern, current and past values domestic money supply, domestic aggregate output, Japan money supply, Japan aggregate output are the main driving forces of the current exchange rate dynamic, in addition to the past values of exchange rates. Furthermore, this study uncovers that rather than the long-perceived linear and symmetrical behavior, the nominal exchange rates adjust towards monetary fundamentals in a non-linear and asymmetrical fashions with respect to appreciation and depreciation of exchange rates, inflation and deflation, expansionary and contractionary monetary policy, as well as the economic cycles of both domestic and Japan countries. Taken together, these findings have important impacts on policy-decision and implementations as pointed out in the last chapter of this study.